Can Brazil produce enough rice to meet demand in 2028? - Pilecco, Isabela Bulegon; Silva, Michel Rocha da; Ribas, Giovana Ghisleni; Junior, Ary Jose Duarte; Streck, Nereu Augusto; Zanon, Alencar Junior (Ciência e Natura, 2022)
The objectives of the study were estimate the additional yield that may be achieved by reducing the yield gap in actual rice area, evaluate if irrigated rice production meet future demand for rice without increase area and determine sowing date that allows maximum yield potential. The yield gap (Yg) was determined by the difference between yield potential (Yp) and actual yield (Ya). The Ya was obtained from surveys applied to the rice producers. The Ya was 51% of Yp, and the Yg was 49%. In a scenario of high demand, if the yields follow the historical rate of gain, the production should not be sufficient to meet projected demand without 6% expansion of the currently cultivated area, whereas for a scenario of low demand it should be sufficient. Moreover, for the low and high demand scenarios, if the national average yield reaches 80% of the rice Yp, a reduction until 29% in the current irrigated rice area can occur. Sowing between September and mid-November is a way of making it possible to obtain yields close to 80% of Yp without increasing production costs. This study can be used as an aid in the search for world food security.